Continuum of Developmental Language Disorders: Where Does PLI Fall? - Shivani Tiwari; Ashwini Bhat; Rajashekar Bellur (Journal of All India Institute of Speech and Hearing, 2008)
Pragmatic Language Impairment (PLI) is a developmental communication disorder, characterized by semantic and pragmatic deficits; relatively adequate phonology and syntax; and mild autistic features. The symptom profile overlaps with Pervasive Developmental Disorder (PDD) and Specific Language Impairment (SLI). The present paper attempts to highlight the differential diagnosis of PLI with common developmental language disorders as SLI and PDD. Two children with speech and language characteristics suggestive of PLI are discussed. Two children (5 yrs each) participated in the study with the complaint of inadequate speech and language skills. Speech and language skills of these two children were evaluated using formal and informal methods.The responses were recorded and were further transcribed for analysis. The obtained profiles of the two children were compared across the profiles of developmental disorders as PLI, SLI and PDD. Case1 presented an early onset, delayed developmental milestones with poor pre-linguistic skills and significant semantic and pragmatic deficits. Case 2, in contrast, showed delayed speech milestones, relatively better pre-linguistic skills and near normal semantic and syntactic skills. Both the cases presented with clear, fluent speech without articulation errors. Pragmatic deficits were prominent in both the cases, with case1 having more severe difficulties. Both case1 and case2 had mildly impaired social skills.Differential diagnosis of PLI with other developmental languagedisorders is controversial issue. PLI shares features of linguistic processing deficits with SLI on one hand, and deficits in pragmatics, social skills and stereotyped repetitive behaviors with PDD on the other hand. There are no well-defined boundaries amongst these disorders. Additionally, course of PLI is such that it changes the diagnostic category as the clinical picture varies with time. The two cases discussed in the present paper had pragmatic deficits in common, though of varied severity and associated features.